ANALYSIS OF CONFLICT SITUATIONS ON DOUBLE-LINE ROUNDABOUT IN FRYDEK-MISTEK (Perner's Contacts, 2011)
The article presents the results of video analysis performed on double-line roundabout in Frýdek-Místek. This paper was prepared with financial support for research and development project No. CG911-008-910 "Influence of structural elements geometry on safety and fluency of operation on roundabouts and possibility of rise crashes prediction”, the Ministry of Transport
Keywords: Video Analysis; Conflict Situation; Roundabout